Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Biologi Di SMA Negeri 2 Langowan - Vilia Emor; Meity Tanor; Danny Ch. Posumah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Studying biology serves as a means to enhance understanding, abilities, perspectives, principles, and ecological accountability. Biology is the scientific discipline that seeks to understand the natural world. Learning biology entails more than simply acquiring factual knowledge, concepts, or principles; it is also an exploratory endeavor. This research aims to discuss problem-based learning (PBL), which can improve the learning outcomes of class XI biology students on plant tissue material and can be used as an alternative learning model. This research uses classroom action research (PTK), which includes four stages: planning, implementing actions, observation,  and reflection, which aim to improve the learning process. PTK is an activity that involves testing an idea in practice, which can improve and increase the quality of the teaching and learning process. The application of the PBL model was able to improve student learning outcomes, especially in biology subjects with plant tissue material for class XI students at SMA N 2 Langowan. During the pre-cycle, the average value was 5.7. In cycle I, it climbed to an average value of 7.3. In cycle II, it further increased to an average value of 8.4. Meanwhile, the completeness of student learning outcomes in the pre-cycle was 20%, while in the first cycle, it was 67%, then grew again in the second cycle, specifically 87%. Based on the aforementioned research findings, it can be inferred that the implementation of the Problem-Based Learning (PBL) model has led to an improvement in the academic performance of Biology students at SMAN 2 Langowan.